Correlation between gestational diabetes mellitus and postpartum cardiovascular metabolic indicators and inflammatory factors: a cohort study of Chinese population - Zhao, Xin; Zhao, Dan; Sun, Jianbin; Yuan, Ning; Zhang, Xiaomei (Frontiers in Endocrinology, 2024)
Objective: This study aimed to analyze the correlation between gestational diabetes mellitus and postpartum metabolic indicators and inflammatory factors, and explore the role of inflammatory factors, so as to provide evidence for the early prevention of postpartum CVD risk in gestational diabetes mellitus.Methods: This prospective study was based on the pregnant women cohort study established in Peking University International Hospital from December 2017 to March 2019. A total of 120 women were enrolled sequentially, including 60 cases of gestational diabetes mellitus (GDM group) and 60 cases of non-gestational diabetes mellitus (non-GDM group) after 4-7 years. The general information, inflammatory factors and metabolic indicators of the women were collected and analyzed.(1) The TyG and siMS levels in the GDM group were higher than those in the non-GDM group (p<0.05, respectively). The interleukin-6(IL-6) levels in the GDM group were higher than those in the non-GDM group and the difference was statistically significant (p<0.05). (2) The results of linear regression analysis showed that GDM was associated with postpartum GLU0min (β=0.94, 95%CI: 0.27-1.60, p<0.05), GLU120min (β=2.76, 95%CI: 1.57-3.94, p<0.05) and HbA1c (β=0.49, 95%CI: 0.27-1.60, p<0.05). At the same time, GDM was significantly correlated with postpartum metabolic indicators triglyceride-glucose (TyG) index (β=0.31, 95%CI: 0.01-0.61, p<0.05) and siMS score (β=0.45, 95%CI: 0.03-0.88, p<0.05).The results of linear regression analysis showed that GDM was significantly correlated with IL-6 (β=0.91, 95%CI: 0.02-1.79, p<0.05). ( 3) Logistic regression analysis showed that 3 GDM was an independent risk factor for postpartum abnormal metabolism (OR=10.62, 95%CI: 1.66-68.17, p<0.05), and an independent risk factor for postpartum high low-density lipoprotein cholesterolemia (OR=3.38, 95%CI:1. 01-11.56, p<0.05). ( 4) The IL-6 had a mediating effect in the association between GDM and postpartum TyG and siMS, with the mediating effect sizes being 20.59% and 30.77%, respectively.This study revealed that GDM history can lead to abnormal glucose and lipid metabolism indexes in postpartum women, affect the levels of postpartum CVD-related metabolic indicators. Meanwhile, IL-6 shows a mediating role, providing important clinical evidence for the prevention and control of CVD in such high-risk populations and the improvement of cardiovascular health.